Assessment of early side effects of radiotherapy in breast cancer patients - Hussein, Elaf A.; Al-Rawaq, Khudair J. (Journal of the Faculty of Medicine Baghdad, 2016)
Background: Breast cancer is the commonest cancer in women. In radiotherapy practice, it comprises 25% of patient caseload. This makes understanding the breast irradiation toxicities of prime importance. Early radiation toxicities occur during treatment and up to six months after treatment finished. Objectives: assessment of the early side effects of adjuvant external beam radiotherapy (EBRT) in breast cancer patients. Patients and Methods: A cross sectional survey with analytic component conducted on 60 patients treated in the oncology teaching hospital of medical city from January to April 2016. Results: The most prevalent toxicities were radiation dermatitis, fatigue, pain, sore throat, nausea, dysphagia, and arm edema. There was a significant difference between prevalence of dermatitis with different radiation doses used. Dermatitis was more prevalent with conventional fractionation (CF), than in hypofractionated radiotherapy. Conclusion: Dermatitis was the most common acute toxicity of radiotherapy in breast cancer patients with prevalence of 81.6 %. It was related to dose fractionation. Fatigue was the 2nd common (70%). It was correlated with disease stage.